An argument for strong positivity of the decoherence functional in the path integral approach to the foundations of quantum theory - Dowker,F; Wilkes,H (AVS Quantum Science, 2022)
We give an argument for strong positivity of the decoherence functional as the correct, physical positivity condition in formulations of quantum theory based fundamentally on the path integral. We extend to infinite systems work by Boës and Navascués that shows that the set of strongly positive quantum systems is maximal among sets of systems that are closed under tensor product composition. We show further that the set of strongly positive quantum systems is the unique set that is maximal among the sets that are closed under tensor product composition.I. INTRODUCTION